2020
DOI: 10.3389/fpsyg.2020.547110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Offensive Effectiveness in Winner and Losing Handball Teams

Abstract: The purpose of this study was to determine differences related to the offensive process between winning and losing teams among teams participating in the European Handball Federation Champions League (EHFCL) in 55 matches across five seasons. The key indicators used in this study are the offensive actions, team possession type and the zones of the field, goals, and shooting effectiveness. A total of 34 indicators were analyzed and compared using Mann-Whitney U tests. Sixteen key indicators are identified to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
10
1
3
Order By: Relevance
“…These data, as it happened with the wings, may be influenced by 7‐m throws. Our research is in line with Ferrari et al 41 who observed, that in the EHF Champions League (EHFCL), more goals were scored in the central zones. Backs do not usually throw in zones far from their natural position, although when they do, the effectiveness is not reduced much.…”
Section: Discussionsupporting
confidence: 93%
“…These data, as it happened with the wings, may be influenced by 7‐m throws. Our research is in line with Ferrari et al 41 who observed, that in the EHF Champions League (EHFCL), more goals were scored in the central zones. Backs do not usually throw in zones far from their natural position, although when they do, the effectiveness is not reduced much.…”
Section: Discussionsupporting
confidence: 93%
“…In another study that analyzed factors affecting wins and losses in the Men's European Championship, AS was found to have significant effects on match results (Ferrari et al, 2020). However, although AS was found to be significantly different between the won and lost matches of women's handball in this study (t= 7.264, p= .000), the regression analysis did not show significant differences.…”
Section: Discussioncontrasting
confidence: 76%
“…The outcome of analysis proves significance of certain factors that are more likely contributed to the winning or losing the game. One of the profound differentiators that has been associated with studies are shooting effectiveness and the number of assists committed [2,25]. Furthermore the finishing zone was also considered by researchers, who claimed advantage of number of 6 meter shots and its efficiency by the winning teams [14].…”
Section: Introductionmentioning
confidence: 99%